An embedding of Schwartz distributions in the algebra of asymptotic functions - Michael Oberguggenberger; Todor Todorov (International Journal of Mathematics and Mathematical Sciences)
We present a solution of the problem of multiplication of Schwartz distributions by embedding the space of distributions into a differential algebra of generalized functions, called in the paper asymptotic function, similar to but different from J. F Colombeau's algebras of new generalized functions.